The Plasmodium liver-stage parasitophorous vacuole: a front-line of communication between parasite and host - Nyboer, Britta; Heiß, Kirsten; Müller, Ann-Kristin (International journal of medical microbiology, 2018)
Here we outline seminal work that contributed to our present understanding of the fundamental dynamic cellular processes of the intrahepatic malarial parasite with both specific host-cell factors and compartments.